Data processing specific features of COOMET supplementary bilateral comparisons - Zakharov, I. P.; Botsiura, O. A.; Zadorozhna, I. (NNC Institute of metrology, 2020)
The article provides examples of the application of electrical resistance standards in metrological practice. Existing methods for their calibration are analyzed. It is established that calibration using a comparator is the most accurate and common method for calibrating electrical resistance standards. A model for transferring the size of the resistance unit in calibration of electrical resistance standards using a comparator is considered. An expression is given for the evaluation of the value of measurand. The procedure for estimating the expanded measurement uncertainty based on the kurtosis method is described, and the uncertainty budget is drawn up. An example of evaluation of the measurement uncertainty in calibration of the resistance coil P321 using a resistance comparator P3015 is given. The coincidence of the obtained results with those got using the Monte Carlo method is shown.
Keywords: supplementary bilateral comparisons; measurement uncertainty; Koesters interferometer; gage block